Corrigendum: Microbiology laboratories involved in disease and antimicrobial resistance surveillance: Strengths and challenges of the central African states - Passoret Vounba; Severin Loul; Ludovic F. Tamadea; Joël F.D. Siawaya (AOSIS, 2023)
No abstract available.